Pengaruh Pengelolaan Kelas Dalam Menciptakan Keefektifan Dalam Proses Pembelajarajan di SDN 18 Tangah Koto - Syukrina, Syukrina; Trisno , Bambang; Netri, Netri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
Classroom management is an effort made by the teacher in preparing everything related to learning activities in order to create a comfortable learning environment to obtain conducive learning. Classroom management is very important in the learning process so that students are more focused during the learning process. This study examines the influence of classroom management in creating effectiveness in the learning process in schools, which is the purpose of this study to describe classroom management planning, classroom management implementation and supporting and inhibiting factors in classroom management. The results of this study are very important for the effectiveness of learning, managing them well then learning activities will also run well so that students can focus and receive learning well at school.